Unconventional Resources Technology Conference, Denver, Colorado, 12-14 August 2013 2013
DOI: 10.1190/urtec2013-160
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Unconventional Reservoir Core at Multiple Scales

Abstract: Tight unconventional reservoirs have become an increasingly common target for hydrocarbon production. Exploitation of these resources requires a comprehensive reservoir description and characterization program to estimate reserves, identify properties which control production and account for fracturability. Multiscale imaging studies from whole core to the nanometer scale can aid in understanding the multiple contributions of heterogeneity, fracture density, pore types, pore connectivity, mineralogy and organi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Scaling relations are based on the seminal work of Mattax and Kyte (1962), where oil recoveries as a fraction of the recoverable oil between two systems are related by using a Љdimensionless-timeЉ approach. The most widely used scaling relation for an oil/water system is defined as follows (Ma et al 1995): (1) where t D is the dimensionless time, k is the permeability, is the porosity, is the IFT, m is the geometric mean of water and oil viscosity, t is the imbibition time, and L a is the characteristic length defined as: (2) where V is the volume of the sample, A i is the area open to imbibition in the ith direction, and d ai is the distance the imbibition front travels from the open face to a no-flow boundary.…”
Section: Lab-scale Si Testmentioning
confidence: 99%
See 2 more Smart Citations
“…Scaling relations are based on the seminal work of Mattax and Kyte (1962), where oil recoveries as a fraction of the recoverable oil between two systems are related by using a Љdimensionless-timeЉ approach. The most widely used scaling relation for an oil/water system is defined as follows (Ma et al 1995): (1) where t D is the dimensionless time, k is the permeability, is the porosity, is the IFT, m is the geometric mean of water and oil viscosity, t is the imbibition time, and L a is the characteristic length defined as: (2) where V is the volume of the sample, A i is the area open to imbibition in the ith direction, and d ai is the distance the imbibition front travels from the open face to a no-flow boundary.…”
Section: Lab-scale Si Testmentioning
confidence: 99%
“…The hierarchical imaging workflow coupled with advanced numerical methods (hereinafter referred to as Digital Rock (DR) technology) allows for 3D mapping of pore geometry, pore connectivity, and mineral and fluid distribution, as well as first-principle-based calculation and upscaling of rock properties. The application of this technology to unconventional reservoirs has been a key focus area for a number of case studies that demonstrate great potential (Walls et al 2012, Alberts et al 2013, Korost et al 2013, Koroteev et al 2014, Fogden et al 2014). Knackstedt et al (2013) showed an image registration method that projects a 2D SEM slice to a 3D microCT image such that an integrated understanding of mineral distribution, porosity, and fluid distribution can be acquired.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation